Advance in Recovery and Application of Bioactive Compounds from Seafood - Jacobsen, Charlotte; Holdt, Susan Løvstad (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Due to the increased focus on circular bioeconomies, the full utilization of marine biomasses, including side streams from the seafood processing industry, as well as the utilization of hitherto unexploited biomasses, such as star fish, mussels, seaweed, and microalgae, are receiving increased attention from both academia and the industry. These marine biomasses contain a wide array of bioactive compounds with beneficial and/or functional health properties, which can be exploited for applications in food, feed, dietary supplements, or pharma. New technologies are being developed for the recovery and preservation of bioactive compounds from these resources. Technologies for preserving perishable bioactive compounds are particularly important during the storage of seafood side streams before extraction as well as during the extraction, concentration, purification, and storage of the extracted compounds. Advanced application refers to new applications of the bioactive compounds in, for example, food products or new technologies for the incorporation of these bioactive compounds in food, feed, dietary supplements, or drugs.